2011
DOI: 10.1002/oa.1158
|View full text |Cite
|
Sign up to set email alerts
|

Non‐specific indicators of stress and their association with age at death in Medieval York: Using stature and vertebral neural canal size to examine the effects of stress occurring during different periods of development

Abstract: Selective mortality can occur towards individuals who survive episodes of physiological stress, such as disease and malnutrition, during development. The skeletal elements affected depend on the timing of these stressful episodes. Studying multiple non-specific indicators of stress can show which periods of development were affected and whether certain periods can be linked with selective mortality. To examine this method a preliminary study of 61 adult individuals from the Medieval population of Fishergate Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…VNC size represents the quality of environmental conditions experienced during growth, with reduced diameters representing episodes of disease and malnutrition which disrupted the genetic growth trajectory (Clark et al, 1986;Watts, 2011). The anteroposterior (AP) and transverse (TR) diameters of the lumbar VNC reach their final adult size by around 3-5 years and 15 years, respectively (Hinck et al, 1966;Watts, 2013).…”
Section: Measuring Childhood Health In Human Skeletal Remainsmentioning
confidence: 99%
“…VNC size represents the quality of environmental conditions experienced during growth, with reduced diameters representing episodes of disease and malnutrition which disrupted the genetic growth trajectory (Clark et al, 1986;Watts, 2011). The anteroposterior (AP) and transverse (TR) diameters of the lumbar VNC reach their final adult size by around 3-5 years and 15 years, respectively (Hinck et al, 1966;Watts, 2013).…”
Section: Measuring Childhood Health In Human Skeletal Remainsmentioning
confidence: 99%
“…Bioarchaeological evidence tends to support the assertion that there is an inverse association between stature and mortality (Gunnell et al, 2001; Kemkes-Grottenthaler, 2005; Steckel, 2005; Watts, 2010), though not without exception (Usher, 2000; DeWitte and Wood, 2008). Gunnell et al (2001) examined the association between stature and mortality in a skeletal sample from northeast England, dating from the 9th through the 19th centuries and found, for both males and females and for all long bones, the odds ratio of death before 30 years of age decreased as long bone length (a proxy for stature) increased.…”
Section: Introductionmentioning
confidence: 98%
“…and the early 20th century and found that among 15–30 years olds, a five centimeter decrease in femur length was associated with a 4.6 percent decrease in the probability of survival. Recently, in a sample from northern England dating between the 10th and 15th centuries, Watts (2010) found that females who failed to survive beyond 25 years of age were significantly shorter than those who did, though there were no statistically significant results for males. On the other hand, Usher (2000) examined osteological material from a 12th century Danish cemetery from the village of Tirup using a multi-state model of health and mortality, and did not find an effect of femur length on risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Variability in the size and form (shape 1 size) of the spinal canal, or neural foramen, and the vertebral body has been the subject of many clinical and paleopathological studies, as it has been associated with conditions such as acquired and developmental spinal stenosis, scoliosis, and spondylolysis (clinical literature: Inufusa et al, 1996;Harrington et al, 2001;Masharawi, 2008Masharawi, , 2012Meijer et al, 2010;Abbas et al, 2010;paleopathological literature: Clark et al, 1986;Watts, 2010). Schmorl's nodes are a relatively common spinal pathology in both clinical and archaeological contexts (clinical literature: Dar et al, 2009;Overvliet et al, 2009;Jang et al, 2010;paleopathological literature: Š laus, 2000;Ü stü ndag , 2009;Klaus et al, 2009).…”
mentioning
confidence: 99%